A Suicidal Death Case with an Unmodified Blank Cartridge Gun - Demirci, Şerafettin; Doğan, Kamil Hakan; Erkol, Zerrin; Günaydın, Gürsel; Deniz, İdris (The Bulletin of Legal Medicine, 2008)
Blank cartridge guns are weapons that are generally considered harmless, the use and sale of them are regulated with the law 5729 and relatively easy to buy/obtain them. In this paper, a 31-year-old male case whose death was due to a suicide originated injury from head with a blank cartridge gun is presented. The autopsy revealed a firearm wound demonstrating symptoms of contact shooting on the right temporal region, fractures in the squamous part of the right temporal bone, epidural and subarachnoidal hemorrhages and contusion in the right temporal lobe. As seen in our case, lethal injuries can be inflicted from contact or near-contact distance shootings by blank cartridge guns. Therefore, the barrels of these guns have to be redesigned to prevent gas exit from the muzzle. Keywords: Blank cartridge guns, death, forensic medicine